Empowering Women: Economic Participation And Leadership Development - Parimala Devi Arivumani (Journal Of Social Science (JoSS), 2024)
Empowering women in economic participation and leadership development remains a critical issue globally, with significant disparities in opportunities and representation. This research aims to investigate the factors influencing women's economic participation and leadership roles through a quantitative approach. They were analyzed using statistical methods, including regression analysis. The results reveal a significant positive correlation between access to education, mentorship programs, and economic empowerment, highlighting that women with leadership training exhibit higher participation in leadership roles. The findings emphasize the importance of policy frameworks and support systems to bridge the gender gap in economic and leadership domains. The conclusion underscores the need for targeted interventions to enhance women's leadership capabilities and economic participation, offering insights for policymakers and stakeholders in promoting gender equality.